Pemisahan Anomali Regional dan Residual Data Gayaberat Studi Kasus di Kota Lama Semarang - Supriyadi Supriyadi; Khumaedi Khumaedi; Sugiyanto Sugiyanto; F Setiaswan (Physics Education Research Journal, 2019)
Research has been carried out using gravity methods to identify subsurface structures in the region of Kota Lama Semarang as a preliminary survey for disaster mitigation purposes. In processing gravity data to identify subsurface structures, several processing stages are carried out. The initial step is to make the initial correction in the form of tide correction and float correction then a further correction is performed until a complete Bouguer anomaly contour is obtained. From the complete Bouguer anomaly, regional and residual gravity anomalies can be separated. The separation of regional anomalies from Bouguer anomalies in this study uses the moving average method while residual anomalies are obtained by subtracting Bouguer anomalies from regional anomalies. In the study of identification of subsurface structures it is important to conduct regional and residual anomaly separations to interpret geological structures and obtain the targets sought. Regional anomaly values in the region of Kota Lama Semarang are between 28.0 mGal - 28.4 mGal while for residual anomalies have between 31.6 mGal - 32.8 mGal.